Steering the formation of supported Pt-Sn nanoalloys by reactive metal-oxide interaction - Neitzel, Armin; Kovacs, Gabor; Lykhach, Yaroslava; Tsud, Nataliya; Kozlov, Sergey M.; Skala, Tomas; Vorokhta, Mykhailo; Matolin, Vladimir; Neyman, Konstantin M.; Libuda, Jörg (RSC Advances, 2016)
The formation of a supported Pt-Sn nanoalloy upon reactive metal-oxide interaction between Pt nanoparticles and a Sn-CeO2 substrate has been investigated by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy in combination with density functional modeling. It was found that Pt deposition onto a Sn-CeO2 substrate triggers the reduction of Sn2+ cations yielding Pt-Sn nanoalloys at 300 K under ultra-high vacuum conditions. Three distinct stages of Pt-Sn nanoalloy formation were identified associated with the growth of (I) ultra-small monometallic Pt particles on a Sn-CeO2 substrate, (II) Pt-Sn nanoalloys on a Sn-CeO2 substrate, and (III) Pt-Sn nanoalloys on a stoichiometric CeO2 substrate. These findings suggest the existence of a critical size of monometallic Pt particles above which the formation of a Pt-Sn nanoalloy becomes favorable. In this respect, density functional modeling revealed a strong dependence of the formation energy of the PtxSn nanoalloy on the size of the Pt particle. Additionally, the thermodynamically favorable bulk and surface Pt/Sn stoichiometries were identified as two parameters that determine the composition of the supported Pt-Sn nanoalloys and limit the extraction of Sn2+ from the Sn-CeO2 substrate. Primarily, the formation of a bulk Pt3Sn alloy phase drives the growth of the Pt-Sn nanoalloy upon Pt deposition at 300 K. Upon annealing, Sn segregation on the surface of the Pt-Sn nanoalloy promotes further extraction of Sn2+ until the thermodynamically stable Pt/Sn concentration ratios of 3 for the bulk and approximately 1.6 for the surface are reached.